1968
DOI: 10.1002/pssb.19680300110
|View full text |Cite
|
Sign up to set email alerts
|

Activation Energies for Zener Relaxation in α‐AgCd

Abstract: Activation energies for Zener relaxation have been measured from 15.0 to 39.6aty0 Cd in Ag with a torsion pendulum, and compared with recent diffusion data over the same range of concentrations. Over most of the range the relaxation energies are approximately 1.5 kcal/mol less than the energy of the faster diffuser; as the solubility limit is approached, however, this energy difference increases. As in earlier work, the relaxation times are approximately equal to the extrapolated mean times of stay of the fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1968
1968
1976
1976

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Also shown schematically in Fig. 2 is the activation energy for the Zener relaxation, from the work of Turner, Dozier, and Williams [4]. The relaxation activation energy is slightly less than the activation energy for diffusion of either tracer.…”
Section: Resultsmentioning
confidence: 99%
“…Also shown schematically in Fig. 2 is the activation energy for the Zener relaxation, from the work of Turner, Dozier, and Williams [4]. The relaxation activation energy is slightly less than the activation energy for diffusion of either tracer.…”
Section: Resultsmentioning
confidence: 99%
“…For the f. c. c. systems the relaxation activation energy is observed to be lower than that for the faster diffusing specie in the alloy. Recent work on the f. c. c. Ag-Cd and Ag-In systems [2,3,41 where accurate diffusion data are available has confirmed that relaxation occurs with a lower activation energy than diffusion.…”
mentioning
confidence: 99%
“…[8], and Shtrakhman and Piguzov[7]. The most The temprrature dependeni-r of the relaxation t i m e fur the Zeiiur relsxatioir in the silver-30at:In content (at %J -Comparison of the relaxation and diffusion activation energies for silver-indium alloys Comparison of the relaxation and diffusion activation energies for silver-cadmium alloys content (at 0interesting feature of the present work is the low relaxation activation energy for the Ag-39 atyo Cd alloy.The mean time of stay of a diffusing cadmium atom can be calculated from the diffusion data of Schoen[3] and Gardner et al[a] from therandomwalk equation Q where f is the correlation factor, a is the lattice parameter, Comparison of the mean times of stay of a cadmium atom using equation (2) with the relaxation time for the Ag-29 atyo Cd and Ag-39 a t % Cd alloy gives an order of magnitude difference and was obtained in the following way.…”
mentioning
confidence: 99%